2019
DOI: 10.1038/s41597-019-0188-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporary dense seismic network during the 2016 Central Italy seismic emergency for microzonation studies

Abstract: In August 2016, a magnitude 6.0 earthquake struck Central Italy, starting a devastating seismic sequence, aggravated by other two events of magnitude 5.9 and 6.5, respectively. After the first mainshock, four Italian institutions installed a dense temporary network of 50 seismic stations in an area of 260 km2. The network was registered in the International Federation of Digital Seismograph Networks with the code 3A and quoted with a Digital Object Identifier (10.13127/SD/ku7Xm12Yy9). Raw data were converted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…This huge number of waveforms is due to the great effort made during the last seismic sequences in 2016 (Amatrice M w 6.0-Visso M w 5.9-Norcia M w 6.5) by the Italian Department of Civil Protection (DPC), the Istituto Nazionale di Geofisica e Vulcanologia (INGV), and several academic and research institutions that installed more than 100 temporary stations with the aim of improving the event locations (Moretti et al, 2017) 25 and monitoring the site effects. 26,27 The same dataset was also adopted for other studies in the area, such as investigations on the temporal variability of ground motion, 28,29 microzonation studies, 26 as well as for calibrating a methodology aiming to identify the reference rock sites. 30 For more stable and robust analyses, we set the threshold to at least 10 recordings for each station, according to Lanzano et al 7 The unselected stations were mainly located at the borders of the study area (additional details are available in Ref.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This huge number of waveforms is due to the great effort made during the last seismic sequences in 2016 (Amatrice M w 6.0-Visso M w 5.9-Norcia M w 6.5) by the Italian Department of Civil Protection (DPC), the Istituto Nazionale di Geofisica e Vulcanologia (INGV), and several academic and research institutions that installed more than 100 temporary stations with the aim of improving the event locations (Moretti et al, 2017) 25 and monitoring the site effects. 26,27 The same dataset was also adopted for other studies in the area, such as investigations on the temporal variability of ground motion, 28,29 microzonation studies, 26 as well as for calibrating a methodology aiming to identify the reference rock sites. 30 For more stable and robust analyses, we set the threshold to at least 10 recordings for each station, according to Lanzano et al 7 The unselected stations were mainly located at the borders of the study area (additional details are available in Ref.…”
Section: Datamentioning
confidence: 99%
“…It consists of more than 30,000 records of about 450 earthquakes in the magnitude range 3.4‐6.5 and more than 460 stations within 120 km from the epicenters. This huge number of waveforms is due to the great effort made during the last seismic sequences in 2016 (Amatrice M w 6.0—Visso M w 5.9—Norcia M w 6.5) by the Italian Department of Civil Protection (DPC), the Istituto Nazionale di Geofisica e Vulcanologia (INGV), and several academic and research institutions that installed more than 100 temporary stations with the aim of improving the event locations (Moretti et al., 2017) 25 and monitoring the site effects 26,27 . The same dataset was also adopted for other studies in the area, such as investigations on the temporal variability of ground motion, 28,29 microzonation studies, 26 as well as for calibrating a methodology aiming to identify the reference rock sites 30 .…”
Section: Datamentioning
confidence: 99%
“…(i) a group of stand-alone seismic stations, as a part of 3A network, was deployed to record the aftershock sequence (Cara et al 2019). Since the historical seismicity in Central Italy is often characterized by long lasting sequences with more than one main shock related to different sectors of the complex fault system of the area 1 3 (Chiaraluce et al 2017;Pizzi et al 2017), the recording stations were equipped with both accelerometric and velocimetric sensors in order to catch high-magnitude events avoiding the signal saturation.…”
Section: Data Collectionmentioning
confidence: 99%
“…To investigate the role of local amplification in Amatrice, the RM1 team installed in the village 4 seismic stations with the aim of recording the aftershocks sequence and, eventually, some other high-magnitude event. These stations were part of a more extended seismic network (code network 3A, https ://doi.org/10.13127 /sd/ku7xm 12yy9 ), based on 50 stand-alone recording stations installed in the epicentral area in cooperation between several research institutes (Cara et al 2019). The 3A network was deployed from September 19th, 2016, and was operative until the end of November 2016, while the seismic sequence was still active but when the earliest emergency phases, based on the rescue operations, were over.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of earthquakes and ambient noise, recorded on the Amatrice terrace and around it for microzonation purposes, has revealed spatial variation of site effects [25,[31][32][33]: the diffuse amplification of ground motion reaches its maximum values in the downtown area, at the western limit of the terrace, with a resonant frequency of about 2.0-2.5 Hz. Here, the amplification is larger in the northern sector and varies from the central part to the edge, where [25] observed a clear directionality of the resonant peak (on the contrary, [34] concluded that maximum directions are linked to the presence of noise sources).…”
Section: Introductionmentioning
confidence: 99%